RELASI HUKUM DAN EKONOMI DALAM PENDEKATAN FILSAFAT - Alamudi, Ichwan Ahnaz (STIS Darussalam Bermi, 2023)
This article is motivated by the law in a study said to be a practical science whose position is certainly special because the pattern as a normative science has its own characteristics in a science. While Economics in history was first assessed as a concrete positive science developed very advanced, without skepticism contributed to a breakthrough in the development of the economy of the people, nation and state.. This article uses a descriptive qualitative approach that is more specific to the data library or library research. In this paper the authors produce that the economy in the context of society is used as a subject of principal as a means to achieve prosperity, because prosperity is a basic entity in humans to meet their needs both goods and services. Then the law is used as the basic instructions, orders, and prohibitions that regulate Order in the composition of society and must be obeyed by those concerned. Furthermore, law and economics were born due to the rapid economic growth in society which causes law to be oriented as an intermediary that limits economic activities in the event of a dispute, which aims at economic progress not to harm the parties either in the rights or interests of the community itself. Keywords: Relations, Law, Economics.